Ventriculoperitoneal Shunt Migration Inside the Gastric Lumen: A Rare Case Report - Sidhu, Jasdeep S (Cureus, 2019)
Ventriculoperitoneal (VP) shunt placement is one of the more common procedures in neurosurgery and has a variety of indications. However, shunt placement can be associated with multiple complications, one of which is proximal and distal shunt migration. There have been reported cases of migration of the distal end of a VP shunt from the intraperitoneal cavity into different organs resulting in a variety of complications. Most of the reported cases are the result of spontaneous migration. However, shunt catheter migration could be iatrogenic as well. We present a case of intragastric VP shunt migration in a patient following placement of a percutaneous endoscopic gastrostomy tube.